Origin of Mutualism Between Termites and Flagellated Gut Protists: Transition From Horizontal to Vertical Transmission - Nalepa, Christine A. (Frontiers in Ecology and Evolution, 2020)
Lower termites, as well as their sister group, the subsocial wood-feeding cockroach Cryptocercus, rely on flagellated eukaryotic symbionts in the hindgut to cooperatively digest their wood diet. In Cryptocercus these flagellates undergo encystment cycles tightly coordinated with the molting cycle of their host, yet the resultant cysts play no demonstrated role in their transmission to neonates; the trophozoite stage of the flagellates is passed directly from parents to offspring via hindgut fluids (proctodeal trophallaxis). This pattern suggests that encystment is a vestige from a gregarious cockroach ancestor, when the flagellates had a functional, two-stage life cycle and the cysts were horizontally transmitted among hosts via coprophagy. The strong integration between flagellate encystment cycles and host developmental physiology in Cryptocercus indicates that the relationship of the flagellates with their proposed gregarious cockroach ancestor was not commensal, but parasitic, with flagellates likely obtaining benefits by taking advantage of host gut metabolites and ingested plant debris. When vertical transmission evolved the parasites were ‘captured’, and their fitness became inescapably embedded in the fitness of their host. The vertical transmission of gut flagellates and the origin of host subsociality via proctodeal trophallaxis can be considered two sides of the same coin. From the host point of view proctodeal trophallaxis marks the origination of parental care by provisioning neonates with nourishment, metabolites and beneficial microbiota. From the flagellate point of view, proctodeal trophallaxis was a shift from horizontal to vertical transmission, pushing them from the parasitic to the mutualistic end of the symbiotic spectrum, arguably making this host behavioral change the most critical juncture in the evolutionary trajectory of the termite lineage.